2010
DOI: 10.1186/1471-2105-11-316
|View full text |Cite
|
Sign up to set email alerts
|

A novel chemogenomics analysis of G protein-coupled receptors (GPCRs) and their ligands: a potential strategy for receptor de-orphanization

Abstract: BackgroundG protein-coupled receptors (GPCRs) represent a family of well-characterized drug targets with significant therapeutic value. Phylogenetic classifications may help to understand the characteristics of individual GPCRs and their subtypes. Previous phylogenetic classifications were all based on the sequences of receptors, adding only minor information about the ligand binding properties of the receptors. In this work, we compare a sequence-based classification of receptors to a ligand-based classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 52 publications
3
39
0
Order By: Relevance
“…This chemogenomics approach not only explained known ‘off-target’ effects of certain ligands, but also predicted relationships unseen by phylogeny alone. These newly-predicted relationships were experimentally validated, extending previous computational efforts to organize GPCRs by their ligand similarity 12 . Although a major advance in the field, the approach cannot identify pharmacological neighbors for orphan GPCRs because it relies upon existing ligand:receptor pairings.…”
mentioning
confidence: 74%
“…This chemogenomics approach not only explained known ‘off-target’ effects of certain ligands, but also predicted relationships unseen by phylogeny alone. These newly-predicted relationships were experimentally validated, extending previous computational efforts to organize GPCRs by their ligand similarity 12 . Although a major advance in the field, the approach cannot identify pharmacological neighbors for orphan GPCRs because it relies upon existing ligand:receptor pairings.…”
mentioning
confidence: 74%
“…Frequently, protein targets are, in the spirit of chemogenomics, classified not according to sequence or fold, but according to the similarity of their ligands. Given a ligand-based classification of protein targets, one can analyze which targets are likely to be hit by a ligand, given its structure [52,53].…”
Section: Chemogenomic Approachesmentioning
confidence: 99%
“…(As discussed above for the ligand side, also for the protein side no single descriptor exists, so sequences, binding pockets and selected subsets of residues in ligand binding pockets have all been used to capture the essential properties of a protein for binding ligands.) In this spirit, groups have employed SVMs [54] as well as substructural analysis [53] in order to relate GPCRs from the ligand-based side -and to estimate how well ligandtarget pairings could be predicted also in cases where no ligands of a particular target are known. In the latter of the above studies [53] it was found that in those cases, 93% of the targets ligands could be identified with a reliability beyond random even if no ligands were given in the training dataset (this resembles a 'receptor deorphanization' setting in practice), thereby illustrating that not only explicitly known ligand-target pairs can be predicted by computational models.…”
Section: Chemogenomic Approachesmentioning
confidence: 99%
“…Private initiatives, such as BioPrint [31], Wombat [32], and MDL Drug Data Report (MDDR) [33], were pioneering in this respect. Therefore, most of the cross-pharmacology analyses reported to date were based either on internal proprietary data [25] or on those commercial databases [15, 23-26]. However, recent efforts on delivering publicly available well-crated chemogenomic databases have finally opened cross-pharmacology analyses to the entire scientific community.…”
Section: Reference Frameworkmentioning
confidence: 99%
“…This information can be exploited in the design of GPCR-directed chemical libraries with optimal coverage across its members [13]. Furthermore, these data have revealed that active GPCR ligands tend to have exceptionally high levels of target promiscuity, in particular for class A aminergic GPCRs [14-17], making chemogenomic strategies especially adequate to GPCR drug discovery [18-23]. …”
Section: Introductionmentioning
confidence: 99%